Facial Recognition of Happiness Is Impaired in Musicians with High Music Performance Anxiety - Sabino, Alini Daniéli Viana; Camargo, Cristielli M.; Chagas, Marcos Hortes N.; Osório, Flávia L. (Frontiers in Psychiatry, 2018)
Music performance anxiety (MPA) can be defined as a lasting and intense apprehension connected with musical performance in public. Studies suggest that MPA can be regarded as a subtype of social anxiety. Since individuals with social anxiety have deficits in the recognition of facial emotion, we hypothesized that musicians with high levels of MPA would share similar impairments. Objective: The aim of this study was to compare parameters of facial emotion recognition (FER) between musicians with high and low MPA. Methods: 150 amateur and professional musicians with different musical backgrounds were assessed in respect to their level of MPA and completed a dynamic FER task. The outcomes investigated were accuracy, response time, emotional intensity, and response bias. Results: Musicians with high MPA were less accurate in the recognition of happiness (p=0.04; d=0.34), had increased response bias toward fear (p=0.03), and increased response time to facial emotions as a whole (p=0.02; d=0.39). Conclusions: Musicians with high MPA displayed FER deficits that were independent of general anxiety levels and possibly of general cognitive capacity. These deficits may favor the maintenance and exacerbation of experiences of anxiety during public performance, since cues of approval, satisfaction, and encouragement are not adequately recognized.